2020
DOI: 10.1002/14651858.cd004770.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Drug therapy for delirium in terminally ill adults

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 103 publications
2
50
0
2
Order By: Relevance
“…Antipsychotic drugs and benzodiazepines are widely used for the treatment of delirium in palliative care. A 2020 Cochrane review of four trials testing drug treatment for delirium in terminally ill adults 276 found that the efficacy of drug therapy was unclear owing to the mostly low to very low quality of evidence in these studies; however, there was some evidence of adverse effects of haloperidol and risperidone.…”
Section: Pharmacological Treatment Of Deliriummentioning
confidence: 99%
“…Antipsychotic drugs and benzodiazepines are widely used for the treatment of delirium in palliative care. A 2020 Cochrane review of four trials testing drug treatment for delirium in terminally ill adults 276 found that the efficacy of drug therapy was unclear owing to the mostly low to very low quality of evidence in these studies; however, there was some evidence of adverse effects of haloperidol and risperidone.…”
Section: Pharmacological Treatment Of Deliriummentioning
confidence: 99%
“…Haloperidol is a major antipsychotic medication prescribed to diminish psychosis in schizophrenia patients 54 . However, its action is limited due to its elicitation of Parkinsonian-like bradykinesia, which affects a majority of patients and is commonly called haloperidol-induced EPS 55 , 56 . To date, there are no effective treatments available for haloperidol-induced EPS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a network meta‐analysis to evaluate pharmacological intervention for delirium treatment 37 and a Cochrane review 38 for drug therapy of delirium in terminally ill adults concluded that pharmacotherapy is not useful in alleviating delirium symptoms. However, if delirium in terminal phase is not being appropriately evaluated, we need to reconsider the conclusion of these meta‐analyses.…”
Section: Discussionmentioning
confidence: 99%